Renyi Holographic Dark Energy And Its Behaviour In F(G) Gravity - Alam, M. K.; Singh, S. S.; Devi, L. A. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In this work, the Renyi holographic dark energy (RHDE) and its behaviour has been explored with the anisotropic and spatially homogeneous Bianchi type-I Universe in the framework of f (G) gravity. We use IR cutoff as the Hubble and Granda-Oliveros (GO) horizons. To find a consistent solutions of the field equations of the models, it is assumed that the deceleration parameter is defined in terms of function of Hubble parameter H. With reference to current cosmological data, the behaviors of the cosmological parameters relating to the dark energy model are evaluated and their physical significance is examined. It is observed that for both the models, the equation of state parameter approaches to -1 at late times. However, the RHDE model with the Hubble horizon exhibits stability from the squared sound speed, but the RHDE model with the GO horizon exhibits instability. In both the models, deceleration parameter and statefinder diagnostic confirm the accelerated expansion of the Universe and also correspond to the λCDM model at late times․ В данной работе исследуется голографическая темная энергия Реньи (RHDE) и ее поведение в анизотропной и пространственно однородной Вселенной типа Бьянки-I в рамках гравитации f (G). Мы используем инфракрасное обрезание как горизонт Хаббла и Гранда-Оливероса (GO). Для нахождения согласованных решений уравнений поля моделей предполагается, что параметр замедления определен в терминах функции параметра Хаббла H. С учетом современных космологических данных оценивается поведение космологических параметров, связанных с моделью темной энергии, и исследуется их физическая значимость. Отмечается, что для обеих моделей параметр уравнения состояния приближается к -1 в позднюю эпоху. Однако модель RHDE с горизонтом Хаббла проявляет стабильность по отношению к квадрату скорости звука, тогда как модель RHDE с горизонтом GO нестабильна. В обеих моделях параметр замедления и диагностический показатель состояния подтверждают ускоренное расширение Вселенной и также соответствуют модели λCDM в позднюю эпоху.
Keywords: Astrophysics